The nexus of family environment with youth street criminal behavior in Khyber Pakhtunkhwa Pakistan - Aman Ullah; Mahrukh Shakir; Nizar Ahmad; Gulrukh Shakir (Heliyon, 2021)
This empirical work focuses on the impact of unsupportive and harsh family practices on youth criminal behaviour. The present study hypothesizes that the harsh practices and low support of a family are the contributing factors for street crimes and that family practices increase the intensity of youth street criminality, particularly in a Pakistani society. While studying youth delinquent behaviour in a Pakistani society, this study employs general strain theory (GST), which has not been employed in any research in Pakistan till date. Thus, the authors examined the variables of the study from the view point of general strain theory (GST). A diverse sample size of 300 street criminals, housed in different jails of Khyber-Pakhtunkhwa (KPK) was selected randomly. However, from each jail, the sample respondents were selected through proportion allocation strategy. Moreover, primary data were collected through structured interviews and analyzed through a series of steps, which involved exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structure equation modeling (SEM). These analyses helped in determining the relationship between family harsh practices, and low family support, with youth participation in street crimes. Findings of this study offer evidence that family harsh practices and low family support directly trigger youth participation in street crimes. The present study does not only confirm the hypothetical statement of GST regarding positive and negative stimuli but also add up the significant contribution in the existing literature from the context of Pakistani society. Initiating awareness programs and sessions regarding different parental skills by sociologist and psychologist on community level, as well as the need for the sociologists and psychologist to provide assistance while addressing psychological issues of offenders are some of the recommendations based on the study findings.